Impact of the COVID-19 pandemic on asthma control among children: a qualitative study from caregivers’ perspectives and experiences - Jingjing Wang; Yuanmin Jia; Jingxian Bao; Mo Yi; Zeyi Zhang; Haixia Wang; Yizhang Li; Ou Chen (BMJ Open)
Objectives To understand the impact of the COVID-19 epidemic on asthma control in children based on caregivers’ perspectives and experiences.Design This was a qualitative study deploying face-to-face, semistructured interviews. Thematic analysis was carried out to analyse the data.Setting Paediatric respiratory clinics in three tertiary hospitals.Participants 16 caregivers providing unpaid asthma-related care and assistance to children under 14 years who had been diagnosed with asthma for more than 1 year and were not only treated with short-acting β2-agonists.Results Six main themes were identified: (1) improved asthma control; (2) decreased willingness to seek medical care driven by fear; (3) increased adherence due to enhanced awareness of asthma control; (4) coping strategies for changes caused by COVID-19; (5) a new opportunity and (6) managing new challenges in asthma control.Conclusions The COVID-19 outbreak and the measures in response to it have had significant impacts on asthma control among children. Children with asthma are advised to continue good asthma management, take their prescribed asthma medications as normal, wash their hands regularly and wear face masks. Regularly supported self-management and remote consultations should be provided during the COVID-19 pandemic. In addition, supporting people financially, providing continued medical support and alleviating any fear and anxiety should be considered. We anticipate that our findings will inform health promotion interventions.